DYNAMICS OF FRICTION COUPLES OF A BAND-SHOE BRAKE - Zhuravlоv, Dmytro; Kindrachuk, Myroslav; Vasylyshyn, Vitaliy; Andreychikov, Yevhen; Burava, Oleksandr; Vasylyshyn, Olga (Problems of Friction and Wear, 2025)
Based on a computational experiment concerning the dynamics of frictional interaction of the pulley rim with a system of linings arranged according to different layout schemes on the belt branches in the belt-pad brake of a drilling winch, the following research results were obtained. The condition of dynamic equilibrium of a flexible brake band with linings in contact with the pulley rim was established with different schemes of their arrangement on the belt. It was proved that with a uniform arrangement of linings, the impulse specific loads in the direction of the approaching belt branch increase by 1.5–3.0 times than in the direction of the converging belt branch. In order to ensure a uniform distribution of impulse specific loads along the arc of contact of the microprotrusions of friction pairs, a method was proposed for determining the values ​​of the lining arrangement angles and their working areas on the belt branches. Recurrent dependencies were obtained for calculating the lining arrangement angles and their area, and therefore, the quantity. This allowed the pulse specific loads in the friction pairs to be quasi-equalized on the belt branches, and as a result, the wear of the working surfaces of the linings.